2023
DOI: 10.4081/gh.2023.1189
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal distribution and geostatistically interpolated mapping of the melioidosis risk in an endemic zone in Thailand

Abstract: Melioidosis, a bacterial, infectious disease contracted from contaminated soil or water, is a public health problem identified in tropical regions and endemic several regions of Thailand. Surveillance and prevention are important for determining its distribution patterns and mapping its risk, which have been analysed in the present study. Case reports in Thailand were collected from 1 January 2016 to 31 December 2020. Spatial autocorrelation was analyzed using Moran’s I and univariate local Moran’s I. Spatial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 24 publications
(30 reference statements)
0
0
0
Order By: Relevance
“…Conversely, tambons initially deemed low-high may transition into high-risk areas because of their proximity to high-risk groups. Notably, the high-risk group was primarily clustered in the northern region, consistent with the findings of Wongbutdee et al [21], who identified a significantly elevated incidence of melioidosis in northern Ubon Ratchathani during 2016-2020. Clustering of melioidosis cases suggests heightened exposure to B. pseudomallei in these areas [43].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Conversely, tambons initially deemed low-high may transition into high-risk areas because of their proximity to high-risk groups. Notably, the high-risk group was primarily clustered in the northern region, consistent with the findings of Wongbutdee et al [21], who identified a significantly elevated incidence of melioidosis in northern Ubon Ratchathani during 2016-2020. Clustering of melioidosis cases suggests heightened exposure to B. pseudomallei in these areas [43].…”
Section: Discussionsupporting
confidence: 89%
“…Geospatial data, which are data with georeferenced coordinates to positions on the Earth's surface, have been utilised to monitor and investigate the risk area of melioidosis occurrence. Several studies have conducted spatial analyses of melioidosis distribution in the endemic regions of Australia [2,18], Thailand [19][20][21], and Laos [22]. Geostatistical modelling has revealed that the range distance of the spatial autocorrelation in a quantitative B. pseudomallei count was 7.6 m [23], and the range distance between positive B. pseudomallei samples was 90.51 m in a rice field [24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation